2016
DOI: 10.1096/fj.201600353r
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock regulates inflammatory arthritis

Abstract: There is strong diurnal variation in the symptoms and severity of chronic inflammatory diseases, such as rheumatoid arthritis. In addition, disruption of the circadian clock is an aggravating factor associated with a range of human inflammatory diseases. To investigate mechanistic links between the biological clock and pathways underlying inflammatory arthritis, mice were administered collagen (or saline as a control) to induce arthritis. The treatment provoked an inflammatory response within the limbs, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 54 publications
3
74
0
2
Order By: Relevance
“…Tamai et al () screened over 1,000 molecules from a Food and Drug Administration‐approved drug library and found that 5% had effects on the circadian clocks of human osteosarcoma epithelial cells (U2OS cell line). Disruptions in circadian rhythms have been associated with several disorders, including sleep (Vanselow et al, ), metabolic (Marcheva et al, ), neurodegenerative (Musiek, ), cardiovascular (Chen & Yang, ), autoimmune/inflammatory disorders (Hand et al, ), and cancer (El‐Athman, Fuhr, & Relógio, ). In this context, the circadian clock itself may become a therapeutic target for these disorders, along with other conditions associated with impaired circadian rhythms, namely, age‐related diseases.…”
Section: The Circadian Clock System In Health and Molecular Mechanismmentioning
confidence: 99%
“…Tamai et al () screened over 1,000 molecules from a Food and Drug Administration‐approved drug library and found that 5% had effects on the circadian clocks of human osteosarcoma epithelial cells (U2OS cell line). Disruptions in circadian rhythms have been associated with several disorders, including sleep (Vanselow et al, ), metabolic (Marcheva et al, ), neurodegenerative (Musiek, ), cardiovascular (Chen & Yang, ), autoimmune/inflammatory disorders (Hand et al, ), and cancer (El‐Athman, Fuhr, & Relógio, ). In this context, the circadian clock itself may become a therapeutic target for these disorders, along with other conditions associated with impaired circadian rhythms, namely, age‐related diseases.…”
Section: The Circadian Clock System In Health and Molecular Mechanismmentioning
confidence: 99%
“…This compound has already been shown to have metabolic effects leading to inhibition of glucagon-induced gluconeogenesis in primary hepatocytes. It has also been demonstrated to have an anti-inflammatory role in fibroblast-like synoviocytes (FLSs), a potential candidate for producing rhythmic inflammatory signals during collagen induced arthritis [149]. KL001 and other clock compounds not only provide a tool for dissection of the molecular clock, but may also aid in the development of circadian based treatment for inflammatory and metabolic diseases [148].…”
Section: The Clock Repressors: Period and Cryptochromementioning
confidence: 99%
“…This pathway controls clock output and rhythmic biological processes. In (Hand et al 2016), disruption of the circadian clock is stated as an aggravating factor associated with a range of human inflammatory diseases. Yu et al (2013) showed the role of circadian clock on Th17 cell differentiation.…”
Section: Resultsmentioning
confidence: 99%